¿Estuvo Ákra Leuké en Carmona? (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We analyze the importance of Western Andalusia in the events of the Second Punic War and we propose the identification of the first Barquide capital in Hispania, Ákra Leuké, with the city of Carmona. The literary sources and monetary hoards provide information that confirms this area as nuclear throughout the war. From Carmo would have been created military settlements in strategic areas of the interior of Cadiz and La Serena (Extremadura) that we could qualify as cleruchias. It is possible that the “libiophenician” coins constitute a testimony of these mercenary settlements.
Keywords: Western Andalucia; Second Punic War; Carthaginians; Romans; Coin Hoards; Military Camps; Cleruchias